2017
DOI: 10.5539/jel.v6n2p101
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Emotional Intelligence Program Training and Study Its Effectiveness on Emotional Intelligence of Adolescents with Emotional and Behavioral Problems That Living in Single Parent Families

Abstract: Development of children and adolescents' personality is strongly affected by their parents, and absence of one of them has an undesirable effect on their development, and makes them vulnerable to later psychological disorders and behavioral problems. The purpose of this study was to develop an emotional intelligence training program and to evaluate its effectiveness on increasing emotional intelligence of adolescents with emotional and behavioral problems that living in single parent families. The study utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
2
4
0
4
Order By: Relevance
“…Moreover, several reviews and meta-analyses provide evidence to consider emotional intelligence as a trainable ability in adults (Hodzic et al, 2018;Kotsou et al, 2019;Mattingly and Kraiger, 2019). Nonetheless, some intervention programs also have found that emotional intelligence can be trained in adolescents (e.g., Motamedi et al, 2017;Viguer et al, 2017;Cantero et al, 2020). In line with our findings, researchers and practitioners should foster the development of students' emotional intelligence, particularly among those who have low-quality relationships with their teachers.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, several reviews and meta-analyses provide evidence to consider emotional intelligence as a trainable ability in adults (Hodzic et al, 2018;Kotsou et al, 2019;Mattingly and Kraiger, 2019). Nonetheless, some intervention programs also have found that emotional intelligence can be trained in adolescents (e.g., Motamedi et al, 2017;Viguer et al, 2017;Cantero et al, 2020). In line with our findings, researchers and practitioners should foster the development of students' emotional intelligence, particularly among those who have low-quality relationships with their teachers.…”
Section: Discussionsupporting
confidence: 84%
“…Hence, it was found that the Emotional Competency Module was highly reliable. This is similar to many previous studies which showed that emotional intelligence training can indeed enhance emotional intelligence (Vijayalaxmi & Kadapatti, 2013;Castillo & Fisher, 2017;Motamedi, Ghobari-Bonab, Beh-pajooh, Shokoohi Yekta, & Afrooz, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, other studies also indicate that emotional intelligence programs or trainings were potentially good in enhancing overall emotional intelligence (Dolev & Leshem, 2017;Castillo & Fisher, 2017;Motamedi, Ghobari-Bonab, Beh-pajooh, Yekta, & Afrooz, 2017;Vijayalaxmi & Kadapatti, 2013). Similarly, enhancing emotional intelligence has been shown to improve behaviours (Dolev & Leshem, 2017), improve the life quality of mothers with children with leukaemia illness (Taghizadeh, Masoompour, & Shrinabadi, 2017), reducing the usage of aggression to solve conflicts violence among adolescence to prevent violence (Garaigordobil & Pena-Sarrionandia, 2015), predict significant changes in confusion, perceived stress, mental health, somatic complaints and vigor (Hodzic, Ripoll, Bernal, & Zenasni, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…La evidencia aportada tiene una implicación fundamental para la prevención del PSU: estudios meta-analíticos y de revisión sistemática han concluido que la IE es una capacidad que puede desarrollarse de forma eficaz por medio de intervenciones guiadas (Hodzic et al, 2018;Kotsou et al, 2019;Mattingly y Kraiger, 2019). Asimismo, algunos estudios en los que se ha trabajado específicamente con población adolescente han encontrado que los programas de intervención que pretenden mejorar la IE, además de ser efectivos aumentando dicha capacidad (Motamedi et al, 2017;Viguer et al, 2017), también tienen repercusiones en otras áreas, como el rendimiento académico (Cantero et al, 2020) y los niveles de agresividad de los adolescentes (Castillo-Gualda et al, 2019;Hojjat et al, 2017).…”
Section: Referenciasunclassified